Impact of ligand esterification on the cytotoxicity against breast cancer cells of ruthenium(II)/dppb pyridinedicarboxylate complexes - de Camargo, Mariana Santoro [UNESP]; De Grandis, Rone Aparecido [UNESP]; Galo, Ayrton Corrêa; Resende, Flávia Aparecida; Marcon, Pedro Henrique Salgado; Ellena, Javier; de Araujo-Neto, João Honorato; Batista, Alzir Azevedo (Elsevier, 2025)
Here we report the synthesis and characterization of five new ruthenium(II) complexes with the general formula [Ru(NO)₂(dppb)], where dppb is 1,4-bis(diphenylphosphino)butane and the NO ligands are derivatives of pyridinecarboxylic acids: picolinic acid (C20), 2,3- (C23), 2,4- (C24), and 2,5-pyridinedicarboxylic acids (C25), as well as the monoester derivative of 2,4-pyridinedicarboxylic acid (C24e), obtained by Fischer esterification. The complexes were characterized by elemental analysis, molar conductivity, cyclic voltammetry, NMR spectroscopy (1H and 31P{1H}), and single-crystal X-ray diffraction (for C23 and C24). The stability of the complexes in solution was confirmed by UV-Vis spectroscopy in DMSO and by 31P{1H} NMR in a DMSO/DMEM mixture (for C24), with no evidence of significant speciation reactions. Biological assays revealed that complexes C20 and C24e exhibit significant cytotoxic activity and selectivity against human breast cancer cell lines (MCF-7 and MDA-MB-231) over non-tumorigenic HaCaT cells. Notably, C20 remained active in three-dimensional spheroid models of MCF-7 cells, showing greater potency than cisplatin. Additionally, both C20 and C24e did not induce mutagenic effects or generate intracellular reactive oxygen species, suggesting alternative mechanisms of cytotoxicity. These findings support the potential of picolinic and esterified pyridinedicarboxylic acid ruthenium(II) complexes as promising antitumor agents.